Parent Brands and Brand Extension Strategies - Al Husni, Mhd Zaid (2013)
Brand equity is the dependent variable discussed in our group project by focusing on the analysis of four steps of CBBE model and further understanding how companies can increase their brand equity in an efficient way. Brand equity of a firm from customers’ perspectives play a very important role to gain their competitive advantages in the market, while at the same time, it is used by marketers to market their new product innovation under the same brand name to target their loyal customers, which is named as brand extension strategy. Moreover, there are risks for companies to enter into a new market segmentation, which would cause financial problems, especially for SMEs due to their limitations and lower brand equity. The cost of entering a new market is estimated to be around USD50million to more than USD100million (Brown, 1985). Therefore, on the vice versa, marketers are making full use of their existing brand equity to advertise their new extensions.